Role of crocin in several cancer cell lines: An updated review - Veisi, Ali (Iran J Basic Med Sci, 2020)
Cancer is a major public health problem worldwide. The most important considerable features of cancer cells are uncontrolled proliferation, up-regulated differentiation, and immortality. Crocin, as a bioactive compound of saffron and as a water-soluble carotenoid has radical scavenging, anti-hyperlipidemia, memory improving, and inhibition of tumor growth effects. The present review was designed to evaluate molecular mechanisms underlying crocin effects against cancer cell lines. Data of this review have been collected from the scientific articles published in databases such as Science Direct, Scopus, PubMed, and Scientific Information Database from 1982 to 2019. According to various literature, crocin inhibits tumor growth, and its spread in several types of cancer including colorectal, pancreatic, breast, and prostate, as well as chronic myelogenous and leukemia. It inhibits telomerase activity, microtubule polymerization, cyclin D1, nuclear factor kappa B (NF-kB), multidrug resistance-associated protein (MRP1), and MRP2 overexpression. Crocin can induce apoptosis through activation of caspase 8, up-regulation of p53 expression, Bax/Bcl-2 ratio, and down-regulation expression of Bcl-2, survivin, and cyclin D1. It also down-regulates matrix metalloproteinase 2 and 9 (MMP2 and MMP9), N-cadherin, and beta-catenin expression, which are involved in tumor invasion and metastasis. Tumor invasion was also inhibited by crocin through increasing E-cadherin expression, cell cycle suppression at G1, G0/G1, S, and G2/M phases. Crocin has therapeutic and preventive effects on cancer cells line. Therefore, it has been suggested that this agent can be administered in patients that suffer from this problem.